Effect of glibenclamide, catechin and ethanolic neem leaf extract on pacreatic beta cell regeneration in alloxan-induced diabetic rat (Journal of Medical Science, 2025)
Background. Type 1 diabetes mellitus is characterized by the destruction of pancreatic β-cells, leading to insulin deficiency and persistent hyperglycemia. This study investigates the regenerative potential of glibenclamide, catechin, and ethanolic neem leaf extract on β-cell function and architecture in alloxan-induced diabetic rats. Material and methods. Thirty-five male Sprague-Dawley rats were divided into five groups: normal control (Group A), diabetic control (Group B), glibenclamide-treated (Group C), catechin-treated (Group D), and ethanolic neem leaf extract -treated (Group E). Diabetes was induced using alloxan monohydrate (150 mg/kg, i.p.), and treatments were administered orally for 14 days. Results and conclusions. Biochemical analysis revealed marked hyperglycemia and hypoinsulinemia in diabetic controls, alongside elevated oxidative stress (↑MDA, ↓GSH, SOD, CAT, TAC, TP) and inflammatory markers (NF-κB, IL-6). Treatment with glibenclamide, catechin, and ethanolic neem leaf extract significantly ameliorated these disturbances, with neem producing the most notable improvements. Ethanolic neem leaf extract -treated rats showed near-normal insulin levels, enhanced antioxidant status, and suppressed inflammatory responses. Furthermore, key regenerative markers (IGF-1, GLP-1, EGF, HGF, and betatrophin) were favorably modulated, particularly in the neem group, indicating stimulation of β-cell neogenesis and survival pathways. Histological examination supported the biochemical findings: ethanolic neem leaf extract-treated pancreases exhibited well-preserved islets and restored tissue architecture, contrasting with the degenerative features seen in diabetic controls. These findings suggest that ethanolic neem leaf extract, beyond its hypoglycemic and antioxidant effects, promotes β-cell regeneration through anti-inflammatory and growth factor-mediated mechanisms. This positions neem as a promising phytotherapeutic agent for diabetes management and β-cell restoration.